Autocorrelação espacial em população natural de Terminalia argentea Mart et Succ. no cerrado de Selvíria, MS - Motta Da Silva, Janete [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP]; Sebbenn, Alexandre Magno (My University, 2004)
The objective of this study was determine the spatial distribution of genotypes of Terminalia argentea Mart et Suce. (Capitão-do-campo) in a natural population, aiming to outline strategy to genetic conservation in situ and ex situ. The population (Terminalia argentea) is located in an area of cerrado on the Teaching and Research Farm of FEIS / UNESP. It was sampled seeds in 30 trees to determine the biochemistry and technological traits. The trees were also located per GPS apparatus, with objective of obtaining geographic coordinate and to analysis the genotype spatial structure from I Moran Index. The analysis of spatial autocorrelations, from I Moran index, indicated the tendency of a larger structure among trees near spatially. In another hand, trees distant spatially showed smaller similarity. The spatial structure was more visible in a ray of 353m.
Spatial autocorrelation in natural population of Terminalia argentea Mart et Succ. in cerrado of Selvíria, MS
Keywords: Genetic structure; I Moran index; Spatial autocorrelation; Terminalia argentea; Tropical tree species; Genetic structures; Moran index; Genes; Research; Forestry